„Svůj pokoj vám dávám…“ Potenciál a výzvy současného pohřbu v Českobratrské církvi evangelické - Jana Hofmanová (Teologická Reflexe)
This article presents results of qualitative research (2023) and offers an interpretation of funerals in the ECCB on the basis of how the clergy themselves approach their preparation and how they perceive their role. Funeral service is seen as a ritual that, through the liturgy but also through the perceptive presence of the ministers, offers authentic participation, as well as a certain grounding in tradition and reframing of the loss experienced. Unlike civil funerals, however, the central theme is not the personality of the deceased, but the Word of God; or rather, the setting of human life in Gospel hope. According to ministers, the task is to comfort and enable bereaved to deal well with a difficult period in their lives which is easier when there is a pastoral relationship and safe space. The ministers focus on the bereaved and on their own authenticity, yet the presence of the deceased and their accompaniment is sometimes surprisingly peripheral to the whole event.